COMPARATIVE STUDY ON THE INTRINSIC ELEMENTS OF THE HOBBIT NOVEL AND MOVIE SCRIPT - Winanda Ayu Ningtyas; Udayani Permanaludin; Dedi Sulaeman (Universitas Islam Negeri Sunan Gunung Djati, 2019)
This research analyzes the comparison of intrinsic elements in the novel and the movie script The Hobbit. this work tells about unexpected adventures. A long journey is one of man's biggest dreams. Break away from the comfort of life, explore the uncharted world, without a definite purpose and guarantee a safe return. This is what make decided them Bilbo, Gandalf, and thirteen Dwarves to meet Smaug, the giant dragon inhabiting the Silent Mountain. In this research, researchers used the Racmat Ddjoko Pradopo theory. Pradopo explained that structuralism is a structure with elements that are closer and every element that has meaning in relation to other elements. The researcher used the comparative method because the object under study was a comparative literary work. In analyzing the data, the researcher analyzed the quotes in the novel that were in accordance with the topic and also the theory used. This study aims to analyze the similarities and differences in intrinsic elements in the novels and scripts of the film The Hobbit. it can be seen that the intrinsic element plays an important role in building the story so that it is conveyed by the reader.Keywords: The Hobbit, Structuralism, Intrinsic Elements, Comparative Studies, Similarities and Differences.